Molecular epidemiology and long-term survival analysis of HIV-1/AIDS patients infected with CRF07_BC, CRF01_AE and subtype B in Taiwan - I-An Jen; Wei-You Li; Shang-Jung Wu; Patricia M. T. Chen; Wei-Lun Liu; Yung-Feng Yen; Cathy Shen Jang Fann; Yi-Ming Arthur Chen (PLoS ONE, 2025)
Previously, we reported that HIV-1 patients infected with CRF07_BC had significantly lower viral loads than those infected with subtype B. Since HIV-1 viral load is associated with AIDS disease progression, the current study was to link multiple clinical and molecular databases, and compare clinical outcomes of HIV-1patients infected with CRF07_BC, CRF01_AE and subtype B in Taiwan. Molecular genotyping data of 2,982 HIV-1/AIDS patients were submitted to Taiwan CDC HIV-1/AIDS case management database. Then the database was linked to Taiwan National Health Insurance Research database and National Cause of Death database from 2000−2016. Subsequently, a subtype-based HIV/AIDS clinical database containing 1,605 patients including 858 (53.5%) subtype B, 690 (43.0%) CRF07_BC and 57 (3.5%) CRF01_AE patients was successfully established and the clinical outcomes and survival of these patients were analyzed. Analysis of transmission route showed this HIV-1/AIDS cohort consists of 761 (47.4%) men who have sex with men (MSM), 132 (8.2%) heterosexuals and 712 (44.4%) injection drug user (IDUs). Survival analysis showed subtype B patients had a significantly lower death rate (8.2%) than CRF07_BC and CRF01-AE patients (22.8% and 22.8%, respectively). The higher death rate for CRF07_BC versus subtype B patients could be largely influenced by transmission route (IDU: 95.7% vs. 3.9%; MSM: 85.8% vs. 2.0%), as well as lower ART uptake rates (69.9% vs. 96.3%). Indeed, subset analysis among IDU patients, CRF07_BC-infected patients had a better 16-year survival rate than patients infected with subtype B (74.3% vs. 45.7%, p < 0.05). Our findings suggest that the transmission route is one major factor influencing death rate, while ART treatment and HIV-1 subtypes may also play important roles. Our study is the largest long-term cohort study of patients infected with CRF07_BC and subtype B in the same geographic region.